Validation and Stability of RP-HPLC Method for the determination of Efavirenz as bulk drug and in Pharmaceautical Formulations - PRADEEP KUMAR,; S.C.DWIVEDI,; ASHOK KUSHNOOR, (International Journal of Pharma and Bio Sciences, 2011)
A rapid, precise, accurate, specific and simple RP-HPLC method was developed for the estimation of Efavirenz in its tablet form. A High performance liquid chromatograph 10AT SHIMADZU- SPD10A, using Phenomenex - Luna RP-18(2),250X4.6mm, 5 mm column, with mobile phase composition of Acetonitrile: Phosphate Buffer [58:42 %(v/v)] was used. The flow rate of 1.0 ml min-1 and effluent was detected at 247 nm. The retention time of Efavirenz was 4.611 minutes. Linearity was observed over concentration range of 500-10000ng ml-1. The Limit of detection and limit of quantification was found to be 157.63ng ml-1 and 477.68ng ml-1 respectively. The accuracy of the proposed method was determined by recovery studies and found to be 98.240 to 101.170 %. The proposed method is applicable to stability studies and routine analysis of Efavirenz in bulk and pharmaceutical formulations. The proposed method was validated for various ICH parameters like linearity, limit of detection, limits of quantification, accuracy, precision, range and specificity.